Xây dựng mô hình áp dụng tiến bộ kỹ thuật phát triển nông lâm nghiệp Miền núi - Bùi, Tuyết Nhung (Bộ Giáo dục và Đào tạo, 2013)
Project selected Cuong Loi commune, Na-Ri district, Bac-Can Province, where knowledge of the people was very backward, the productivity of agricultural production was very low, forest was not protected, slash and burn cultivation was a common practice, as a place to implement this project. Using mainly PRA and RRA methods in this evaluation, the followinq conclusions are withdrawn. The acceptable model for rice production is to replace old, low yielding varieties by new and high yielding varieties, such as CR203. Kim Cuong, and Trach Phong Chiem, and to combine an adequate NPK (80:80:40 + 10 tons of animal manure) application. Changing crop patterns from one rice crop per year to rice-peanut (or soybean, corn) has appeared very effective. New varieties provided by project produce from 1.4 to 3 times higher yielda compared to the old ones. Gardening, aqro-forestry inter-cropping models, and improved animal breeding (Laisind cow, Rhodri chicken) models, have also contributed to hunger elimination and poverty alleviation in this area.